2002
DOI: 10.1902/jop.2002.73.7.762
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive Benefits of Subantimicrobial Dose Doxycycline in the Management of Severe, Generalized, Chronic Periodontitis

Abstract: The supplementation of hygienist-delivered full mouth subgingival and supragingival debridement with a host-modulating agent, SDD, provides clinically and statistically significant benefits in the reduction of deep pockets in patients with severe, generalized periodontitis. In addition, adjunctive SDD is more effective than a placebo in preventing further increases in probing depth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
105
0
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(115 citation statements)
references
References 19 publications
6
105
0
4
Order By: Relevance
“…In several studies, the inhibitor effects of doxycycline on matrix degrading MMP activities have been demonstrated (7,8). The results have indicated that this host-modulating antibiotic as an adjunct to SRP has also provided more successful clinical healing results than SRP alone (47,55). Recently, one of these studies has shown that improvements in PD and CAL were significantly greater with adjunctive SDD than with adjunctive placebo and it was concluded that the adjunctive use of doxycycline with SRP is more effective than SRP alone, which is in contrast to our findings (55).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In several studies, the inhibitor effects of doxycycline on matrix degrading MMP activities have been demonstrated (7,8). The results have indicated that this host-modulating antibiotic as an adjunct to SRP has also provided more successful clinical healing results than SRP alone (47,55). Recently, one of these studies has shown that improvements in PD and CAL were significantly greater with adjunctive SDD than with adjunctive placebo and it was concluded that the adjunctive use of doxycycline with SRP is more effective than SRP alone, which is in contrast to our findings (55).…”
Section: Discussionmentioning
confidence: 99%
“…Systemic tetracycline/doxycycline treatment combined with mechanical treatment has been shown to improve clinical parameters, reduce probing depth, and gain clinical attachment in adult or refractory periodontitis patients (13,(41)(42)(43)(44)(45)(46). A recent study has shown that the supplementation of fullmouth subgingival d e b r i d e m e n t w i t h a h o s t -m o d u l a t i n g a g e n t , subantimicrobial dose doxycycline (SDD), provides clinically and statistically significant benefits in the reduction of deep pockets in patients with severe periodontitis (47). However, other studies have shown good results without the use of an adjunctive antibiotic (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…Subantimicrobial 2.5 ± 1.9 (1.2-4.1) 6.9 ± 1.9 (5.2-7.9) Clinical loss of attachment (mm) 1.9 ± 0.5 (1.2-2.4) 5.5 ± 1.3 (3.5-6.9) Bleeding on probing (%) 5.32 ± 3.71 (3.78-8.56) 57.9 ± 14.6 (44.2-68.8) No. of teeth with periodontitis 4.12 ± 1.32 (3.24-6.89) 10.31 ± 1.32 (9.06-12.08) doses of doxycycline inhibit MMP-8 and reduce periodontal disease activity (Caton et al, 2001;Novak et al, 2002). Gingival crevicular MMP-8, -9 levels in periodontitis were higher than those in healthy subjects.…”
Section: Discussionmentioning
confidence: 98%
“…Increased production of a given cytokine is associated with carriage of a risk genotype. Previously, the risk of having periodontal disease has been related to carriage of rare alleles of single cytokine and receptor molecule genes such as IL-1, TNF-a, IL-6 and CD-14 (Caton et al, 2001;Novak et al, 2002;Miller et al, 2006;Rai et al, 2007). MMPs are derived predominantly from polymorphonuclear leukocytes during acute stages of periodontal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…MMP inhibitors such as low dose formulations of doxycycline have been used in combination with scaling and root planing or surgical therapy (Gapski, et al, 2004). In addition, high-risk patient populations such as diabetics or patients with recurrent periodontal disease have benefited from systemic MMP administration (Chang, et al, 1996, Golub, et al, 2001, Novak, et al, 2002. Encouraging results have been shown using soluble antagonists of TNF and IL-1 delivered locally to periodontal tissues in nonhuman primates .…”
Section: Future Host Modulatory Approachesmentioning
confidence: 99%